Hot air treatment reduces postharvest decay in Chinese bayberries during storage by affecting fungal community composition. (February 2021) - Dai, Kun; Han, Peipei; Zou, Xiurong; Jiang, Shu; Xu, Feng; Wang, Hongfei; Wei, Yingying; Shao, Xingfeng
Graphical abstract: Highlights: Dynamics of the microbiome on Chinese bayberry during cold storage are described. The fungal communities on Chinese bayberry are affected by hot air treatment. Richness and diversity of fungal communities are maintained on HA treated fruit. HA treatment reduces the pathogens Botryotinia and Diaporthe on Chinese bayberry. The endophytes Botryosphaeria and Mycosphaerella are increased on HA treated fruit. Abstract: Chinese bayberry fruit were treated with hot air (HA) at 48 ℃ for 3 h and then stored at 4 ℃ for 15 d. Changes in fungal communities were analyzed by high-throughput sequencing (HTS), and decay and fruit quality were monitored during storage. The results showed that HA treatment effectively maintains fruit quality and the richness and diversity of fungal communities. Heat treatment inhibited decay development and reduced the growth of fungi in the genera Botryotinia spp., Davidiella spp., Hanseniaspora spp., and Candida spp. Canonical correspondence analysis further revealed that Botryotinia spp. and Davidiella spp. were positively correlated with fruit decay and weight loss. FUNGuild analysis demonstrated that HA-treated bayberries had a lower relative abundance within the plant pathogen guild, but higher relative abundance within the endophyte guild. The results suggest that HA treatment reduces pathogens by favoring the increase of endophytes, providing new insight into the decay development and quality changes during the storage of postharvest Chinese bayberries.